The Risk Assessment Tools as Technology in Accounting and Economics Decision Making (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Advances in accounting technology and economic decision-making have resulted in many important risk assessment tools that support the decision making process. In the past, risk assessment depended on personal opinions and manual analysis, which often resulted in inaccurate estimates and delays in decision-making. However, with these risk assessment tools, we can now identify, analyze, and mitigate various risks that can affect financial and economic outcomes in a more accurate and efficient manner. This study aims to discuss technology in the form of risk assessment tools as an aid in decision-making and identify trending topics related to the use of risk assessment tools from 2020-2025, particularly in Indonesia. This study uses a qualitative approach and collects data from the scopus database of 1.827 articles selected from 2020 to 2025. In understanding research from the scopus database, bibliometric analysis was used in this study and using analysis tools such as R Studio and Vos Viewer. The results of the study show a significant increase in publications related to risk assessment tools with a growing trend toward international collaboration. The dominant themes that emerged include decision making, artificial intelligence, climate change, health risks, and financial markets. In addition, the increasing number of publications with international collaboration trends shows that the use of risk assessment tools has become a global standard that Indonesia needs to adapt. The government can use these findings as a basis for formulating policies that are more adaptive to technological developments.